Glass fiber and composition for glass fiber

By optimizing the composition of the glass composition, increasing the MGO content and the viscosity of the loss of the temperature, the problem of being lost during the spinning process of high MGO glass compositions, realizing the glass fiber with high modules and small diameter. Production.

CN119330603APending Publication Date: 2025-01-21NIPPON SHEET GLASS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411500367.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2022-08-04
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively spin into glass fibers with small diameters, especially glass compositions containing high MgO content, which are prone to devitrification during the manufacturing process, resulting in frequent manufacturing problems.

Method used

By optimizing the components of the glass composition, ensuring that the content of MgO is above 15% and that the common logarithmic value of the viscosity η [dPa·s] at the devitrification temperature is above 2.6, the spinning performance of the glass fiber can be improved.

Benefits of technology

It realizes the production of glass fibers with high Young's modulus and small diameter, solves the problem of devitrification of high MgO glass compositions during the spinning process, and improves the stability and efficiency of manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102430250000021
    Figure BDA0005102430250000021
  • Figure BDA0005102430250000022
    Figure BDA0005102430250000022
  • Figure BDA0005102430250000031
    Figure BDA0005102430250000031
Patent Text Reader

Abstract

Provided is a glass fiber having a fiber diameter of 18 [mu] m or less, the glass fiber comprising a glass composition, the content of MgO in the glass composition being 15 mol% or more, and the common logarithmic value (log [eta]) of the viscosity [eta] [dPa.s] at the devitrification temperature of the glass composition being 2.6 or more. Furthermore, provided is a glass composition containing, in mol%, 50 to 65% of SiO2, 5 to 26% of Al2O3, 0 to 1.6% of B2O3, 15 to 30% of MgO, 0 to 8% of CaO, 0 to 2.4% of Li2O, and more than 0.2% but 2.85% or less of Na2O, the total content of Li2O, Na2O, and K2O being 0.3 to 3.0% or less, and the ratio of the content of Na2O to the total being 0.2 to 0.95 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of August 4, 2022, Chinese application number 202280006762.5, and invention name “Glass Fiber and Composition for Glass Fiber”. Technical Field

[0002] The present invention relates to glass fibers and glass compositions suitable for glass fibers. Background Art

[0003] Most of the glass fibers used in practice are composed of glass compositions having a Young's modulus of 90 GPa or less. However, glass compositions having a Young's modulus exceeding 90 GPa are also known. For example, Patent Document 1 discloses a glass composition containing a large amount of rare earth oxides. 2 O 3 La 2 O 3 The total content of rare earth oxides is in the range of 20 to 60 weight %. However, if the content of rare earth oxides is high, the manufacturing cost increases. In view of this, Patent Document 2 discloses a technology for increasing the Young's modulus of a glass composition without requiring a large amount of rare earth oxides. The glass composition of Patent Document 2 contains 15 to 30% of MgO expressed in mole % as a component for increasing the Young's modulus.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2006 / 057405

[0007] Patent Document 2: Japanese Patent No. 6391875 Summary of the invention

[0008] Problems to be solved by the invention

[0009] It is difficult to spin a glass composition containing 15 mol% or more of MgO as a component that increases the Young's modulus (referred to as "high Mg glass" in this paragraph) into glass fibers with a small fiber diameter. Even with high Mg glass that can be spun into glass fibers with a relatively large fiber diameter, manufacturing problems will frequently occur if the fiber diameter is reduced. High Mg glass is prone to devitrification in a nozzle used to spin glass fibers with a small diameter. Therefore, an object of the present invention is to provide a new glass fiber with a high Young's modulus and a relatively small diameter. Another object of the present invention is to provide a glass composition suitable for glass fibers with a high Young's modulus and a relatively small diameter.

[0010] Means used to solve problems

[0011] The present inventors have repeatedly studied the mechanism of devitrification when spinning a glass composition having a high MgO content, and have completed the present invention.

[0012] The present invention provides a glass fiber having a fiber diameter of 18 μm or less.

[0013] The glass fiber includes a glass composition, wherein the content of MgO in the glass composition expressed in mol% is 15% or more, and the common logarithm logη of the viscosity η [dPa·s] of the glass composition at the devitrification temperature is 2.6 or more.

[0014] From another aspect, the present invention provides a glass composition for glass fiber, wherein:

[0015] Expressed in mole % it contains:

[0016]

[0017] Li 2 O、Na 2 O and K 2 The total content of O is 0.3 to 3.0% or less.

[0018] According to Na 2 O content relative to Li 2 O、Na 2 O and K 2 The total ratio of O content to Na 2 The O ratio is 0.2 or more and 0.95 or less.

[0019] From another aspect, the present invention provides a glass composition for glass fiber, wherein:

[0020] Expressed in mole % it contains:

[0021]

[0022]

[0023] The common logarithm value logη of the viscosity η [dPa·s] at the devitrification temperature is 2.6 or more.

[0024] From another aspect, the present invention provides a glass composition for glass fiber, wherein the Young's modulus is greater than 93 GPa, wherein:

[0025] Expressed in mole %,

[0026] Li 2 O、Na 2 O and K 2 The total content of O is 0.3 to 3.0% or less.

[0027] According to Na 2 O content relative to Li 2 O、Na 2 O and K 2 The total ratio of O content to Na 2 The O ratio is 0.2 or more and 0.95 or less.

[0028] Effects of the Invention

[0029] According to the present invention, there is provided a novel glass fiber having a high Young's modulus and a relatively small diameter. According to the present invention, there is provided a novel glass composition suitable for a glass fiber having a high Young's modulus and a relatively small diameter. DETAILED DESCRIPTION

[0030] The following describes an embodiment of the present invention, but the following description is not intended to limit the present invention to a specific embodiment. In this specification, the contents of the components of the following glass compositions are all expressed in mol%, and mol% is basically expressed as "%". In this specification, "substantially free of" and "substantially free of" mean that the content is less than 0.1 mol%, less than 0.05 mol%, less than 0.01 mol%, less than 0.005 mol%, and further less than 0.003 mol%, and depending on the circumstances, less than 0.001 mol%. The main idea of ​​"substantially" is that trace amounts of impurities from glass raw materials, manufacturing equipment, etc. are allowed to be contained. "Alkali metal oxide" refers to Li 2 O、Na 2 O and K 2 O, sometimes written as R 2 O. The upper and lower limits of the content described below can be arbitrarily combined.

[0031] [Fiberglass]

[0032] In one embodiment of the present invention, the fiber diameter of the glass fiber is 18 μm or less. The glass fiber comprises a glass composition, wherein the content of MgO in the glass composition is 15% or more, and the common logarithm value logη of the viscosity η [dPa·s] at the devitrification temperature of the glass composition is 2.6 or more. An example of the glass composition will be described later.

[0033] In another embodiment of the present invention, the glass fiber includes a glass composition described below. The fiber diameter of the glass fiber may be 18 μm or less.

[0034] The fiber diameter of the glass fibers of these embodiments (hereinafter referred to as "glass fibers of the present embodiment") can be 15 μm or less, 13 μm or less, 11 μm or less, 10 μm or less, 9 μm or less, and further 7 μm or less. The glass fibers of the present embodiment can have a high Young's modulus, and therefore can exhibit a high reinforcing ability even if the diameter is reduced. Therefore, the glass fibers of the present embodiment are particularly suitable for thin reinforced materials, such as thin glass fiber reinforced plastics (FRP). However, the objects for which the glass fibers of the present embodiment are used are not limited to FRP, and there is no restriction on the thickness of the objects. The lower limit of the fiber diameter of the glass fibers of the present embodiment is not particularly limited, and can be 3 μm or more, and further 7 μm or more. The glass fibers of the present embodiment can have a high Young's modulus and a thin diameter, or can have a diameter in a range that is not too thin, such as a diameter in the range of 7 to 15 μm, and further 9 to 13 μm.

[0035] The glass fiber of the present embodiment may include a glass composition and components such as various known treatment agents and resins appropriately added according to the application.

[0036] [Glass composition]

[0037] <Ingredients>

[0038] Hereinafter, each component that can constitute the glass composition will be described.

[0039] (SiO 2 )

[0040] SiO 2 It is a component that forms the skeleton of glass, and is also a component that adjusts the devitrification temperature and viscosity when forming glass and improves acid resistance. 2 The content of SiO is, for example, 50 to 65%. 2 The lower limit of the content is, for example, 52% or more, 54% or more, 55% or more, 56% or more, 57% or more, 57.5% or more, and in some cases, 58% or more, or further 59% or more. SiO 2 The upper limit of the content is, for example, 63% or less, 62% or less, or in some cases, 61% or less.

[0041] (Al 2 O 3 )

[0042] Al 2 O 3 It is a component that adjusts the devitrification temperature and viscosity when forming glass and improves the water resistance of glass. 2 O 3 The content of Al is, for example, 5 to 26%. 2 O 3The lower limit of the content is, for example, 7.5% or more, 8% or more, 9% or more, 10% or more, 10.5% or more, 11% or more, 12% or more, and in some cases, 12.5% ​​or more, or further 13% or more. 2 O 3 The upper limit of the content is, for example, 20% or less, 18% or less, 17.5% or less, 16% or less, or in some cases, 15% or less.

[0043] (MgO)

[0044] MgO is a component that contributes to the improvement of Young's modulus and affects the devitrification temperature, viscosity, etc. The content of MgO is, for example, 15 to 30%. The lower limit of the content of MgO is, for example, 16% or more, 17.5% or more, 18% or more, 20% or more, 22% or more, and depending on the situation, 23% or more, and further 24% or more. The upper limit of the content of MgO is, for example, 27% or less, 26% or less, and depending on the situation, 25% or less.

[0045] SiO 2 、Al 2 O 3 As described above, the content rate of Ag and MgO can be set by arbitrarily combining the above upper limits and lower limits, but the desirable ranges are as follows.

[0046] Example 1SiO 2 :52~62% and Al 2 O 3 :7.5~26%

[0047] Example 2 In Example 1, Al 2 O 3 :9~26%

[0048] Example 3 In Example 2, SiO 2 :55~62%

[0049] Al 2 O 3 :10.5~17.5%

[0050] MgO: 17.5~30%

[0051] Example 4 In Example 3, Al 2 O 3 :11~17.5%

[0052] MgO: 20-30%

[0053] However, the above are merely examples, and the content of each component may be set without being limited to Examples 1 to 4.

[0054] SiO 2、Al 2 O 3 , and MgO are important components from the perspective of forming a practical glass composition having a high Young's modulus. The total content of these components exceeds 90%, and may be 91% or more, or further 92% or more. SiO 2 、Al 2 O 3 The total content of MgO can be, for example, 98.5% or less, or further 98% or less. If the total content is suppressed to this extent, there is more room for adjusting the characteristics by adding other components.

[0055] The glass composition of this embodiment preferably further contains CaO and / or alkali metal oxides. A glass composition with a high MgO content tends to have a viscosity η at a devitrification temperature that is too low. However, the viscosity can be adjusted by adding CaO and alkali metal oxides. The total content of CaO and alkali metal oxides is, for example, 0.1% or more, 0.5% or more, 1.0% or more, or 1.5% or more.

[0056] (CaO)

[0057] CaO is a component that adjusts the devitrification temperature and viscosity when forming glass. The content of CaO is, for example, 0 to 8%. The lower limit of the content of CaO is, for example, 0.1% or more, 0.5% or more, 0.7% or more, 1% or more, and depending on the situation, 2% or more, and further 3% or more. The upper limit of the content of CaO is, for example, 6% or less, 5.5% or less, 5% or less, and further 4% or less.

[0058] (Alkali Metal Oxides)

[0059] Alkali metal oxides (R 2 O) is a component for adjusting the devitrification temperature and viscosity when forming glass. The total content of alkali metal oxides, specifically Li 2 O+Na 2 O+K 2 O is, for example, 0.3 to 3.0%. The lower limit of the content of the alkali metal oxide is, for example, 0.5% or more, 0.7% or more, further 0.8% or more, and in some cases, 1.0% or more. The upper limit of the content of the alkali metal oxide is, for example, 2.5% or less, 2.0% or less, 1.8% or less, 1.5% or less, and in some cases, less than 1.1%. When the content of the alkali metal oxide is high, there is a case where the Young's modulus cannot be sufficiently increased.

[0060] Na 2 The content of O is, for example, greater than 0.2% and less than 3%, or greater than 0.2% and less than 2.85%. 2The lower limit of the O content is, for example, 0.25% or more, 0.3% or more, 0.4% or more, or further 0.5% or more. 2 The upper limit of the O content is, for example, 2.5% or less, 2.0% or less, 1.5% or less, 1.0% or less, 0.8% or less, in some cases 0.6% or less, and further 0.55% or less.

[0061] Not necessarily contain Li 2 O and K 2 O, but preferably contains at least one. Li 2 O and K 2 The total content of O is preferably 0.1% or more.

[0062] Li 2 The content of O is, for example, 0 to 3%, or, for example, 0 to 2.4%. 2 The lower limit of the content of O is, for example, 0.1% or more, 0.2% or more, and in some cases, 0.3% or more. 2 The upper limit of the O content is, for example, 2.0% or less, 1.5% or less, 1.0% or less, 0.8% or less, and in some cases, 0.6% or less, 0.5% or less, or further 0.4% or less. 2 A preferred example of the O content is 0.1 to 0.8%.

[0063] Regarding the adjustment of properties such as devitrification temperature while suppressing the influence of lowering Young's modulus, Li 2 O than Na 2 O and K 2 Therefore, when adding 0.3% or more of an alkali oxide to a glass composition in order to achieve a high Young's modulus, the Li 2 The content of O is higher than that of Na 2 O content and K 2 For example, in each example of Patent Document 2, when the content of the alkali metal oxide is 0.3% or more, Li is added. 2 O to its content ratio is higher than Na 2 O content and K 2 The content of O is as high as 0.45% or more.

[0064] However, in order to effectively control the viscosity at the devitrification temperature, it is desirable to give priority to the Na 2 O ratio. In addition, Li 2 O is relatively expensive among alkali metal oxides. Considering these aspects, Li 2 The O content can be no higher than that of Na 2The content obtained by adding 2% to the content of O contains a trace amount of Li. 2 The O content can also be less than Na 2 The content of O includes a trace amount within the range.

[0065] K 2 The content of O is, for example, 0 to 2.4%. 2 The lower limit of the content of O is, for example, 0.01% or more, further 0.02% or more, and in some cases 0.05% or more. 2 The upper limit of the O content is, for example, 1.0% or less, 0.5% or less, 0.2% or less, or in some cases, 0.1% or less. 2 O and Li 2 O and Na 2 Compared with O, the effect of reducing Young's modulus is greater. 2 The content of O is preferably suppressed to be less than that of Li 2 O content and Na 2 O content. K 2 O may not be substantially contained.

[0066] For the relative size relationship of the alkali metal oxides shown in the above two paragraphs, [Li 2 O] represents Li 2 O content (mol%), [Na 2 O] means Na 2 The content of O (mol%) is determined by [K 2 O] represents K 2 The content rate (mol %) of O can be expressed as follows: The alkali metal oxide is preferably contained so as to satisfy at least one of the following formulae.

[0067] 0<[Li 2 O]≤([Na 2 O]+2)

[0068] 0<[Li 2 O]≤[Na 2 O]

[0069] [K 2 O]<[Na 2 O]

[0070] [K 2 O]<[Li 2 O]

[0071] In R 2 When the total content of O is 0.3% or more, more specifically, in the range of 0.3 to 3.0%, Na 2 O content relative to R2 The ratio of the content of O (according to the above-mentioned recording method, [R 2 O] / [Na 2 O], hereinafter also referred to as "Na 2 O ratio) is preferably 0.2 or more and 0.95 or less. 2 When the O ratio is adjusted to an appropriate range, the spinnability of the glass composition having a high MgO content is improved. 2 The lower limit of the O ratio may be, for example, 0.22 or more, 0.27 or more, or further 0.3 or more. 2 The upper limit of the O ratio may be, for example, 0.92 or less, 0.86 or less, 0.8 or less, 0.78 or less, 0.73 or less, or 0.7 or less in some cases. 2 O ratio, the desired effect, such as a sufficient increase in logη, can be obtained by adding a limited amount of alkali metal oxide.

[0072] That is, it is preferred if [R 2 O] represents the content (mol %) of the alkali metal oxide, the following relationship holds.

[0073] 0.3≤R 2 O]≤3.0

[0074] 0.2≤([Na 2 O] / [R 2 O])≤0.95

[0075] (B 2 O 3 )

[0076] B 2 O 3 It is a component that forms the skeleton of glass and is also a component that adjusts the devitrification temperature and viscosity when forming glass. 2 O 3 The content of B is, for example, 0 to 1.6%. 2 O 3 The lower limit of the content is, for example, 0.1% or more, 0.5% or more, or in some cases, 1.0% or more. 2 O 3 The upper limit of the content is, for example, less than 1.5%, and in some cases less than 1.2%. 2 O 3 It is not necessary to substantially contain it.

[0077] (Y 2 O 3 La 2 O 3 )

[0078] Y2 O 3 La 2 O 3 These are components that contribute to the improvement of Young's modulus. However, the raw materials of these components are relatively expensive. 2 O 3 La 2 O 3 The total content of Y is, for example, 0 to 0.5%, or further 0 to 0.3%. 2 O 3 La 2 O 3 The upper limit of the total content of Y can be 0.1% or less. 2 O 3 La 2 O 3 Each may not substantially contain.

[0079] (Other ingredients)

[0080] The glass composition may contain components other than the above. Examples of other components that may be contained in the glass composition include SrO, BaO, ZnO, TiO 2 、ZrO 2 , Fe 2 O 3 , Cl 2 、F 2 SnO 2 、CeO 2 , P 2 O 5 、SO 3 The content of these components is, for example, 0 to 5%. The upper limit of the content may be 3% or less, 1% or less, or further 0.5% or less. 2 to La 2 O 3 The components other than the components may be substantially free of each other. The total content of other components may be 7% or less, 5% or less, or further 3% or less. It should be noted that the content of components that can have multiple valences in the glass composition is calculated by converting them into oxides of the valences shown above according to the conventional method. For example, part of iron oxide may exist in the glass composition in the form of FeO, but its content is converted into Fe 2 O 3 And express.

[0081] <Features>

[0082] In one embodiment of the present invention, the common logarithm of the viscosity η of the glass composition at the devitrification temperature is, for example, 2.6 or more. The unit of η is [dPa·s]. In addition, the present invention includes a technique for improving a glass composition having a Young's modulus of, for example, 93 GPa or more. The following describes logη and Young's modulus.

[0083] (logη)

[0084] It has been found that a glass composition with high logη is suitable for spinning glass fibers with relatively small fiber diameters. For example, logη is 2.6 or more. The lower limit of logη may be 2.7 or more, 2.8 or more, 2.9 or more, 2.93 or more, and may be 3.0 or more depending on the situation. The upper limit of logη is not particularly limited, and is, for example, 3.4 or less, and further, 3.2 or less.

[0085] Glass compositions with a high MgO content and suitable for improving Young's modulus tend to have a smaller difference between the operating temperature suitable for spinning and the devitrification temperature. Glass compositions with a small difference between the two temperatures are generally difficult to spin, and are particularly difficult to spin for glass fibers with small fiber diameters. However, such difficulty in spinning can be alleviated by controlling logη.

[0086] (Young's modulus)

[0087] The Young's modulus of the glass composition is, for example, 93 GPa or more. The lower limit of the Young's modulus is 95 GPa or more, 97 GPa or more, 99 GPa or more, and in some cases, 100 GPa or more. The upper limit of the Young's modulus is not particularly limited, and is, for example, 115 GPa or less, and further, 110 GPa or less.

[0088] <Examples of glass compositions>

[0089] In one embodiment of the present invention, the glass composition comprises:

[0090]

[0091] Li 2 O、Na 2 O and K 2 The total content of O is 0.3 to 3.0% or less, and the Na 2 O content relative to Li 2 O、Na 2 O and K 2 The total ratio of the content of O is 0.2 or more and 0.95 or less.

[0092] In another embodiment of the present invention, the glass composition comprises:

[0093]

[0094] logη is greater than 2.6.

[0095] In another embodiment of the present invention, the glass composition has a Young's modulus of 93 GPa or more, wherein:

[0096] Li 2 O、Na 2 O and K 2 The total content of O is 0.3 to 3.0% or less, and the Na 2 O content relative to Li 2 O、Na 2 O and K 2 The total ratio of the content of O is 0.2 or more and 0.95 or less.

[0097] In another embodiment of the present invention, in the glass composition,

[0098] SiO 2 、Al 2 O 3 and the total content of MgO expressed in mol % exceeds 90%,

[0099] The common logarithm value logη of the viscosity η [dPa·s] at the devitrification temperature is 2.6 or more.

[0100] The above descriptions of the components and properties are all applicable to the glass compositions in each form exemplified above.

[0101] The glass compositions in the above-mentioned forms are suitable for the manufacture of glass fibers, especially glass fibers whose fiber diameters reach the above-mentioned range. In one embodiment of the present invention, the glass fibers contain the glass compositions in the above-mentioned forms, or are composed of the glass compositions in the above-mentioned forms. The glass fibers may be, for example, in a form that conforms to at least one selected from bundled yarns, rovings, spinnings, cloths, chopped strands, glass wool, and milled fibers. Cloths are, for example, roving cloths and spinning cloths. However, the glass compositions in the above-mentioned forms can also be used in the form of glass molded bodies other than glass fibers due to their excellent properties. An example of a glass molded body is granular glass. Granular glass can be manufactured by breaking glass fibers; or it can be manufactured using a nozzle corresponding to the target shape in the same manner as glass fibers. Therefore, the glass compositions in the above-mentioned forms are also suitable for manufacturing granular glass while avoiding devitrification. In one embodiment of the present invention, the granular glass contains the glass compositions in the above-mentioned forms, or is composed of the glass compositions in the above-mentioned forms.

[0102] The granular glass may be, for example, at least one selected from the group consisting of flaky glass, glass powder, glass beads, and fine flakes. The granular glass may also be used for FRP, that is, for reinforcing a body to be reinforced, such as a resin.

[0103] [Non-woven fabrics, rubber reinforcing wire]

[0104] Each glass fiber provided by the present invention can be used for the same purpose as the existing glass fiber. According to one embodiment of the present invention, a glass fiber nonwoven fabric containing glass fibers is provided. In addition, according to one embodiment of the present invention, a rubber reinforcing wire material containing a bundled yarn formed by bundling glass fibers is provided. The glass fiber can also be used for other purposes. Other uses include the reinforcement of a reinforced body represented by a resin.

[0105] Example

[0106] Hereinafter, the embodiment of the present invention will be described in more detail by way of examples and comparative examples. In addition, in Tables 1 to 3, the content ratios of the compositions are also expressed in mol %.

[0107] <Glass compositions of compositions A to H and W to Z>

[0108] Common glass raw materials such as silica sand are prepared in the form of the compositions shown in Table 1, and the batch materials of the glass raw materials are respectively prepared in the examples and comparative examples. Using an electric furnace, each batch material is heated to 1500-1600°C to melt it, and this state is maintained for about 4 hours until the composition becomes uniform. Then, a part of the molten glass (glass melt) is flowed onto an iron plate, and slowly cooled to room temperature in an electric furnace to obtain a glass composition (plate-like object, glass sample) in the form of a block. For these glass compositions, the characteristics are evaluated as described below. The results are shown in Table 1.

[0109] (Devitrification temperature)

[0110] The glass composition crushed to a particle size of 1.0 to 2.8 mm is placed in a platinum boat and kept in an electric furnace with a temperature gradient (800 to 1400°C) for 2 hours. The devitrification temperature is calculated based on the maximum temperature of the electric furnace corresponding to the position where the crystal appears. In the case where the glass becomes turbid and crystals cannot be observed, the maximum temperature of the electric furnace corresponding to the position where the turbidity appears is taken as the devitrification temperature. Here, the particle size is a value measured by a sieving method. It should be noted that the temperature (temperature distribution in the electric furnace) that varies depending on the location in the electric furnace is pre-determined, and the glass composition placed in a specified location in the electric furnace is heated at the pre-determined temperature of the specified location.

[0111] (Viscosity at devitrification temperature)

[0112] The viscosity η of the obtained glass composition at the devitrification temperature was measured by a common platinum ball pulling method, and logη was calculated from the measured value.

[0113] (Young's modulus)

[0114] The Young's modulus is calculated by measuring the longitudinal wave velocity vl and the transverse wave velocity vt of elastic waves propagating in the glass by a conventional ultrasonic method, and using the density ρ of the glass measured separately by the Archimedean method, E=3ρ·v t 2 ·(v l 2 -4 / 3·v t 2 ) / (v l 2 -v t 2 ) formula to find out.

[0115] <Spinning test>

[0116] For each glass composition having compositions A to E and W to Z, a spinning test was performed in which a melt was spun using a platinum nozzle.

[0117] The results of the spinning test were evaluated based on the following criteria.

[0118] ○: Stable spinning suitable for production can be performed for a long time.

[0119] △: Spinning can be performed for 10 minutes or more, but long-term stable spinning cannot be achieved.

[0120] ×1: The platinum nozzle used was clogged due to devitrification.

[0121] ×2: The viscosity of the molten glass is too low to allow spinning.

[0122] <Adjustment of alkali metal oxide>

[0123] Glass compositions were prepared in the same manner as above with respect to compositions C1 to C2 and compositions D1 to D4 in which only the content of alkali metal oxides was changed, respectively, using compositions C and D as references, and their properties were evaluated.

[0124] As shown in Table 2, it can be confirmed that the logη of compositions W and X is small and is not suitable for spinning of fibers with a diameter of less than 18 μm. For compositions Y and Z, spinning itself cannot be performed. In contrast, for compositions A to E with a logη of 2.6 or more, it can be confirmed that even fibers with a small diameter can be spun well. As shown in Table 3, Na 2 O ratio (molar ratio Na 2 O / R 2O) is closer to about 0.5, the larger the logη is. It is believed that in order to make logη reach an appropriate Na of 2.6 or more 2 O ratio is 0.2 to 0.95, and further 0.2 to 0.8. However, it can be confirmed from the composition W in Table 1 that in the alkali metal oxide R 2 In a composition with too low an O content, even if Na 2 O ratio, and the contribution to the increase of logη is not large. It should be noted that the Young's modulus of compositions A to H is slightly lower than that of compositions W to Z, but is large enough for general-purpose glass fiber compositions.

[0125] The operating temperatures of glasses A to H are in the range of 1268 to 1356° C. The difference between the operating temperature and the devitrification temperature of glasses A to H is less than 60° C. This also applies to glasses D2 to D4. The operating temperature is a temperature at which logη becomes 3.0.

[0126] [Table 1]

[0127]

[0128] [Table 2]

[0129]

[0130] ×1: Blockage due to devitrification ×2: Unable to form a thread

[0131] [Table 3]

[0132] Composition / characteristics C1 C C2 D1 D2 D D3 D4 <![CDATA[SiO 2 ]]> 57.5 57.5 57.5 55.0 55.0 55.0 55.0 55.0 <![CDATA[Al 2 THE 3 ]]> 12.5 12.5 12.5 14.5 14.5 14.5 14.5 14.5 <![CDATA[B 2 THE 3 ]]> 1.0 1.0 1.0 1.5 1.5 1.5 1.5 1.5 MgO 24.5 24.5 24.5 23.0 23.0 23.0 23.0 23.0 CaO 4.0 4.0 4.0 5.0 5.0 5.0 5.0 5.0 <![CDATA[Li 2 The]]> 0.5 0.25 0.00 0.90 0.75 0.5 0.3 0.1 <![CDATA[Na 2 The]]> 0.25 0.50 0.10 0.25 0.6 0.8 1.0 <![CDATA[K 2 The]]> 0.02 0.02 0.10 0.10 0.1 0.1 0.1 <![CDATA[R 2 The]]> 0.5 0.52 0.52 1.10 1.10 1.1 1.1 1.1 <![CDATA[Na 2 O / R 2 O]]> 0.00 0.48 0.96 0.09 0.23 0.50 0.68 0.86 Devitrification temperature(℃) 1360 1331 1378 1312 1308 1295 1317 1340 logη 2.50 2.93 2.41 2.53 2.72 2.90 2.74 2.62 Young's modulus(GPa) 100.5 100.2 100.4 100.7 100.5 100.2 100.2 100.3

Claims

1. A glass fiber having a fiber diameter of 18 μm or less, The glass fiber comprises a glass composition, the content of MgO in the glass composition expressed in mol% is 15% or more, and the common logarithm value of the viscosity η of the glass composition at the devitrification temperature is 2.6 or more, in, The unit of viscosity η is dPa·s.

2. The glass fiber according to claim 1, wherein The total content of SiO 2 , Al 2 O 3 and MgO in the glass composition expressed in mol % exceeds 90%.

3. The glass fiber according to claim 1, wherein The total content of CaO and alkali metal oxides in the glass composition, expressed in mol %, is 0.1% or more.

4. The glass fiber according to claim 1, wherein The glass composition has a Young's modulus of 93 GPa or more.

5. The glass fiber according to claim 4, wherein The Young's modulus is greater than 95 GPa.

6. The glass fiber according to claim 5, wherein The Young's modulus is greater than 99 GPa.

7. The glass fiber according to claim 1, wherein The logη is greater than 2.

7.

8. The glass fiber according to claim 1, wherein The content of MgO in the glass composition expressed in mol% is 20% or more.

9. The glass fiber according to claim 1, wherein The total content of Li2O, Na2O and K2O in the glass composition expressed in mol% is 0.3% to 3.0%, The Na2O ratio determined as the ratio of the Na2O content expressed in mol % to the total content of Li2O, Na2O, and K2O is 0.2 or more and 0.95 or less.

10. The glass fiber according to claim 1, wherein The content of Li2O in the glass composition expressed in mol% is 0.1% to 0.8%.

11. The glass fiber according to claim 1, wherein The total content of Y2O3 and La2O3 in the glass composition expressed in mol% is 0% to 0.5%.

12. The glass fiber according to claim 1, wherein The fiber diameter of a single fiber is 13 μm or less.

13. A glass composition for glass fiber, wherein: Expressed in mole % it contains: The total content of Li2O, Na2O and K2O is 0.3% to 3.0% or less. The Na2O ratio determined from the ratio of the Na2O content to the total content of Li2O, Na2O, and K2O is 0.2 or more and 0.95 or less.

14. The glass composition according to claim 13, wherein: The total content of SiO2, Al2O3 and MgO expressed in mol% exceeds 90%.

15. The glass composition according to claim 13, wherein: The content of B2O3 expressed in mol% is 0.1% to 1.6%.

16. The glass composition according to claim 15, wherein: The content of SiO2 expressed in mol% is 57% to 62%.

17. The glass composition according to claim 13, wherein: The content of SiO2 expressed in mol% is 52% to 62%, The content of Al2O3 expressed in mol% is 7.5% to 26%.

18. The glass composition according to claim 17, wherein: The content of Al2O3 expressed in mol% is 9% to 26%.

19. The glass composition according to claim 18, wherein: Expressed in mole %, The content of SiO2 is 55% to 62%. The content of Al2O3 is 10.5% to 17.5%, The content of MgO is 17.5% to 30%.

20. The glass composition according to claim 19, wherein: Expressed in mole %, The content of Al2O3 is 11% to 17.5%. The content of MgO is 20% to 30%.

21. The glass composition according to claim 13, wherein: The content of Li2O expressed in mol% is 0.1% to 0.8%.

22. The glass composition according to claim 13, wherein: The total content of Y2O3 and La2O3 in the glass composition expressed in mol% is 0% to 0.5%.

23. A glass composition for glass fiber, wherein: Expressed in mole % it contains: SiO2 50%~65%, Al2O3 5%~26%, B2O3 0%~1.6%, MgO 15%~30%, CaO 0%~8%, Li2O 0% or more and less than 3%, Na2O is greater than 0.2% and less than 3%, The common logarithm value of the viscosity η at the devitrification temperature is 2.6 or more, The unit of viscosity η is dPa·s.

24. The glass composition according to claim 23, wherein: The logη is greater than 2.

7.

25. The glass composition according to claim 23, wherein: The content of MgO expressed in mol% is 20% or more.

26. A glass composition for glass fiber, having a Young's modulus of 93 GPa or more, wherein: Expressed in mole %, The total content of Li2O, Na2O and K2O is 0.3% to 3.0% or less. The ratio of the content of Na2O to the total content of Li2O, Na2O, and K2O is 0.2 or more and 0.95 or less. The glass composition according to claim 26 , which has a Young's modulus of 99 GPa or more.

28. A glass fiber comprising the glass composition according to any one of claims 13 to 27.

29. The glass fiber according to claim 28, wherein The fiber diameter is 18 μm or less.

30. The glass fiber of claim 28, wherein The fiber has a form that conforms to at least one selected from the group consisting of bundled yarn, roving, spun yarn, cloth, chopped strands, glass wool, and milled fiber.

31. The glass fiber according to any one of claims 1 to 12, wherein The fiber has a form that conforms to at least one selected from the group consisting of bundled yarn, roving, spun yarn, cloth, chopped strands, glass wool, and milled fiber.

32. A rubber reinforcing wire material comprising a bundled yarn formed by bundling the glass fibers according to claim 28.

33. A rubber reinforcing wire material comprising a bundled yarn formed by bundling the glass fibers according to any one of claims 1 to 12.

34. A glass fiber nonwoven fabric comprising the glass fiber according to claim 28.

35. A glass fiber nonwoven fabric comprising the glass fiber according to any one of claims 1 to 12.

36. A particulate glass comprising the glass composition according to any one of claims 13 to 27.

Citation Information

Patent Citations

  • Information recording and reproducing device

    JP1988091875A

  • Rubber-reinforcing cord and rubber belt using same

    WO2006057405A1